Structural Factors Affecting Exchange Rate Volatility : A Cross-Section Study - Canales Kriljenko, Jorge (IMF Working Papers; Working Paper ;, 2004)
The paper examines factors affecting exchange rate volatility, with an emphasis on structural features of the foreign exchange regime. It draws for the first time on detailed survey data collected by the IMF on foreign exchange market organization and regulations. Key findings are that decentralized dealer markets, regulations on the use of domestic currency by nonresidents, acceptance of Article VIII obligations, and limits on banks' foreign exchange positions are associated with lower exchange rate volatility. The paper also provides support for earlier results on the influence of macroeconomic conditions and the choice of exchange rate regime on volatility.